Correlational analysis of parental occupation on students’ agripreneurial competency skills and choice of agribusiness after graduation in Abubakar Tafawa Balewa University Bauchi, Nigeria - Abdulhamid, U.; Shagori, Y. Ilesha; Jurbe , Zabe; Abdullahi, B. Bala; Ilugbo, T. Hassan; Mamman, J. Jirgi; Altine , Garba; Ekpo, J. Cyril; Saulawa, U. Bishir; Tukur, U. Mohammed (Kashere Journal of Education, 2023)
The broad objective of the study is to determine the relationship of parental occupation on students’ agripreneurial competency skills and choice of agribusiness after graduation. The study adopted a descriptive survey design with a population of 196 final year agricultural technology students of 2018/2019 session of the Abubakar Tafawa Balewa university, Bauchi. The sample size for the study was one hundred (100) students that were randomly selected. A self-developed questionnaire was designed and administered for data collection. The questionnaire was validated by three lecturers from the Faculty of Technology Education and Faculty of Agriculture and Agricultural Technology. The Alpha Cronbach’s reliability coefficient was 89.56% which was highly reliable. Data obtained was subjected to descriptive statistics and cross-tabulation. The frequency result indicated that majority of the students do not possess agribusiness skills. There was a significant association between parental occupation and agribusiness competency skills possessed by the students, i.e., students’ whose parents are civil-servants wants to be civil-servants and students whose parents are full-time farmers does want to be farmers.